Comparison of Blood and Tissue Eosinophil Count and Blood IgE in Patients with Chronic Sinusitis and Nasal Polyps - Masoud Asghari; Shadi Izadpanahi; Mina Heidari Esfahani (Journal of Immunology Research)
Background. The inflammatory mucosa of the sinus cavities is called sinusitis and is divided into various types based on its appearance and sign. Chronic rhinosinusitis is an inflammatory-infectious disease that involves the frontal, sphenoid, ethmoid, and maxillary sinuses. Chronic sinusitis is a multifactorial disease and the range of causes varies from environmental factors to genetic factors. The purpose of this study was to compare blood and tissue eosinophils and serum IgE levels in patients with chronic sinusitis with nasal polyp in Vali-e-Asr hospital in 1397. Methods. In this descriptive-analytical study, the population under study included those with chronic sinusitis referred to Birjand Valiasr Hospital in 1397.3 cc of blood samples were taken 1 day before surgery to evaluate eosinophil counts and serum IgE levels. Also, samples taken from patients during surgery were counted, and then, 100 cells were counted, and eosinophil counts and percentages were calculated. The data were entered into the SPSS software after data collection. Results. This study was performed on 70 patients with chronic rhinosinusitis which included 43 men (61.4%) and 27 women (38.6%) with mean age of 39.11±13 13.72 years. There was no significant difference between sex of patients and mean serum IgE level (P<0.05). The mean percentage of eosinophils in blood samples and tissues of patients with chronic sinusitis was significantly increased with the increase in CT scan (P<0.05). Conclusions. Tissue or blood eosinophilia was not observed in patients with chronic rhinosinusitis. Also, the mean eosinophil percentage of blood and tissue increased significantly in patients with increased scanning computed tomography (P<0.05).